Induction of Programmed Cell Death in Acanthamoeba culbertsoni by the Repurposed Compound Nitroxoline - Rodríguez-Expósito, Rubén L; Sifaoui, Ines; Reyes-Batlle, María; Fuchs, Frieder; Scheid, Patrick L; Piñero, José E; Sutak, Robert; Lorenzo-Morales, Jacob (Antioxidants (Basel, Switzerland), 2023)
Acanthamoeba is a ubiquitous genus of amoebae that can act as opportunistic parasites in both humans and animals, causing a variety of ocular, nervous and dermal pathologies. Despite advances in Acanthamoeba therapy, the management of patients with Acanthamoeba infections remains a challenge for health services. Therefore, there is a need to search for new active substances against Acanthamoebae. In the present study, we evaluated the amoebicidal activity of nitroxoline against the trophozoite and cyst stages of six different strains of Acanthamoeba. The strain A. griffini showed the lowest IC50 value in the trophozoite stage (0.69 ± 0.01 µM), while the strain A. castellanii L-10 showed the lowest IC50 value in the cyst stage (0.11 ± 0.03 µM). In addition, nitroxoline induced in treated trophozoites of A. culbertsoni features compatibles with apoptosis and autophagy pathways, including chromatin condensation, mitochondrial malfunction, oxidative stress, changes in cell permeability and the formation of autophagic vacuoles. Furthermore, proteomic analysis of the effect of nitroxoline on trophozoites revealed that this antibiotic induced the overexpression and the downregulation of proteins involved in the apoptotic process and in metabolic and biosynthesis pathways.
Keywords: cytoskeleton; nitroxoline; Acanthamoeba; programmed cell death; proteomic analysis; autophagy